Identification and comparison of oligopeptides during withering process of White tea by ultra-high pressure liquid chromatography coupled with quadrupole-orbitrap ultra-high resolution mass spectrometry. (July 2019) - Zhao, Feng; Ye, Naixing; Qiu, Xiaohong; Qian, Jiang; Wang, Danhong; Yue, Wenjie; Zuo, Zecheng; Chen, Mingjie
Abstract: Peptides could have specific tastes or bioactivities depending on the length and sequence of amino acids. Till date it remains unknown what peptides are formed during the white tea manufacturing process and whether they contribute to the flavor or bio-activities of white tea. As a first step to address these questions, we applied ultra-high pressure liquid chromatography coupled with quadrupole-orbitrap ultra-high resolution mass spectrometry (UPLC-Quadrupole-Orbitrap-UHRMS) to monitor peptides dynamic changes during the withering process. A total of 196 abundant peptides were identified. Most of them were oligopeptides within a molecular weight of 1000 Da. Four of them were randomly selected, synthesized peptides were applied for further confirmation and quantification. Sequence analysis suggested that some of them were potential taste contributors. Proteinase cleave site analysis identified two separate periods of active proteins degradation at 0–12 h and 30–42 h of the withering processes. Further analysis of cleavage sites also suggested that protein degradation during withering steps were random rather than a stepwise reaction. Graphical abstract: Unlabelled Image Highlights: This is the first survey on peptide changes during withering process of white tea. Two periods of active protein degradation were identified at 0–12 h and 30–42 h. A total of 196 peptides were identified, protein cleavage sites were also analyzed. Protein degradation during withering process was simultaneous rather than stepwise.